2006
DOI: 10.4049/jimmunol.177.8.5471
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Pathway of Bony Fish Complement: Identification of Two Homologs of the Mannose-Binding Lectin Associated with MASP2 in the Common Carp (Cyprinus carpio)

Abstract: The lectin pathway of complement is considered to be the most ancient complement pathway as inferred from identification of ancient homologs of mannose-binding lectin (MBL) and MBL-associated serine proteases (MASPs) in some invertebrates. MBL homologs with galactose selectivity and an MASP3-like sequence also occur in bony fish, linking the evolution of the lectin complement pathway from invertebrates to higher vertebrates. However, these cannot be considered authentic complement components until confirmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 52 publications
(41 reference statements)
1
35
1
Order By: Relevance
“…The crucial role of MASP-1 was surprising considering that both birds and fish seem to have lost the MASP-1-encoding exons by secondary genetic events subsequent to expansion of the MASPs (47)(48)(49). Previous results indicating that MASP-2 does not need help for activation have been confounded by the presence of activated MASP-2 in the preparations, for example (4), a problem we identified and then solved through coexpression of MASP-2 with C1 inhibitor.…”
Section: Discussionmentioning
confidence: 94%
“…The crucial role of MASP-1 was surprising considering that both birds and fish seem to have lost the MASP-1-encoding exons by secondary genetic events subsequent to expansion of the MASPs (47)(48)(49). Previous results indicating that MASP-2 does not need help for activation have been confounded by the presence of activated MASP-2 in the preparations, for example (4), a problem we identified and then solved through coexpression of MASP-2 with C1 inhibitor.…”
Section: Discussionmentioning
confidence: 94%
“…25,75 MBLs were also purified from rohu (L. rohita), rainbow trout (O. mykiss), sea lamprey (Petromyzon marinus), common carp (Cyprinus carpio), fugu (T. rubripes), and turbot (Scophthalmus maximus). [76][77][78][79][80] Moreover, MBL gene from channel catfish (Ictalurus punctatus) was upregulated following the exposure to gram-negative pathogens. 80 In the African catfish, Clarias gariespinus, MBL exhibited antimicrobial activity and in tilapia (O. niloticus), it induced cytochine production.…”
Section: -Ballarin-9780128032527mentioning
confidence: 99%
“…The MBL-A/MBL-C duplication was probably an independent event in the mammalian lineage. 77 The three identified and partially characterized rainbow trout MBL homologues represent structural homologues of mammalian MBLs and are expressed in various tissues including the anterior intestine, the liver, and spleen. A rainbow trout MASP-3 homologue was also expressed in partially overlapping tissues.…”
Section: Mbl Phylogeny and Evolutionmentioning
confidence: 99%
“…The MBL and ficolins have three similar domains: a cysteine-rich N-terminal region, a collagenous region characterized by Gly-X-Y repeats (X and Y stand for any amino acids) (Dodds and Matsushita, 2007), and a neck region. The major differences between them include fewer repeats of Gly-X-Y within ficolin and a fibrinogen-like domain within the C-terminal region of ficolin (Matsushita and Fujita, 2002;Atkinson et al, 2004;Nakao et al, 2006;Runza et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The lamprey is the most primitive animal found to possess the MBL Dodds and Matsushita, 2007). Two types of the MBL group have been characterized in the bony fish: one has a QPD-type galactose-binding CRD (with Gln-Pro-Asp motif) and is designated GalBL, and the other has an EPN-type mannose-binding CRD and is designated MBL (Vitved et al, 2000;Nakao et al, 2006;Jackson et al, 2007). Previous studies have shown that GalBL was probably mutated from an MBL extra copy and has since acquired galactose-binding capability (Nonaka and Smith, 2000).…”
Section: Introductionmentioning
confidence: 99%